Terrorizing gender: transgender visibility and the surveillance practices of the U.S. security state - Fischer, Mia (Expanding frontiers: Interdisciplinary approaches to studies of women, gender, and sexuality, 2019)
"Using an interdisciplinary framework, Fischer connects media coverage with the state regulation of trans people to show how, despite some increase in positive depictions, negative representations of trans people as deceptive, deviant, and threatening still permeate mass-mediated discourses used to justify, even normalize, state-sanctioned violence against gender non-conforming populations"--